Normative and Cultural Approach in Strengthening the Integrity of the KPK as an Independent Institution - Riska Dwi Romina; Aan Fardani Ubaidillah (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2025)
This study explores the normative and cultural approaches in strengthening the integrity of the Corruption Eradication Commission (KPK) as an independent institution amid legislative and political dynamics. The normative dimension is examined through the lens of legal changes following the enactment of Law No. 19 of 2019, which significantly altered KPK’s institutional structure, authority, and operational independence. Simultaneously, the cultural approach is discussed in relation to the internal organizational values and ethical codes that shape KPK's work environment and commitment to anti-corruption. Employing a qualitative library research method, this article highlights how legal paradoxes and bureaucratic constraints have weakened KPK's independence, while underscoring the vital role of cultural reinforcement such as ethical leadership, value internalization, and anti-corruption education in maintaining public trust and institutional effectiveness. The findings affirm that the synergy between a strong normative foundation and a resilient organizational culture is essential for upholding KPK’s legitimacy and performance as a guardian of integrity in Indonesia’s governance system.